2015
DOI: 10.1016/j.renene.2015.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation at pilot plant scale of multiple PCMs (cascaded) vs. single PCM configuration for thermal energy storage

Abstract: a b s t r a c tThe present paper provides on one hand, a literature review of the different studies available in the scientific literature where the concept of multiple phase change materials (PCM) configuration, also named cascaded or multi-stage, has been presented and on the other hand, an experimental evaluation of the advantages of using the multiple PCM configuration instead of the single PCM configuration in thermal energy storage (TES) systems at pilot plant to fill the gap of experimental and high sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…The experiments were conducted with vertical shell and tube type heat exchanger devices under realistic operation parameters and were used for a numerical model to simulate different cascaded storage configurations. Recently, Peiro et al performed an experimental evaluation of the advantages of using the cascaded PCM configuration with melting temperature in the range of 150°C to 200°C instead of the single PCM configuration in TES systems. The results showed that the cascaded PCM configuration led to a 19.36% improvement in efficiency.…”
Section: Heat Transfer Enhancement Technologiesmentioning
confidence: 99%
“…The experiments were conducted with vertical shell and tube type heat exchanger devices under realistic operation parameters and were used for a numerical model to simulate different cascaded storage configurations. Recently, Peiro et al performed an experimental evaluation of the advantages of using the cascaded PCM configuration with melting temperature in the range of 150°C to 200°C instead of the single PCM configuration in TES systems. The results showed that the cascaded PCM configuration led to a 19.36% improvement in efficiency.…”
Section: Heat Transfer Enhancement Technologiesmentioning
confidence: 99%
“…One of the most important issues in the study of heat exchangers are the calculation of the amount of stored heat transfer and the production power. The heat transfer rate ( ) obtain from the Equation (1) [22,23]:…”
Section: Appendix Governing Equations Of Heat and Power Transfer Ratementioning
confidence: 99%
“…However, the solidification rate was found to be prolonged in such eccentric configurations, thereby extending the energy retrieval rate 37 38 by incorporating the fins (extended surfaces), 39 by the multiple PCM method, 40 and by microencapsulation/macroencapsulation 41‐44 …”
Section: Introductionmentioning
confidence: 99%